Ameliorating Effects of Transcutaneous Electrical Acustimulation at Neiguan (PC6) and Zusanli (ST36) Acupoints Combined with Adaptive Biofeedback Training on Functional Outlet Obstruction Constipation. (24th September 2020) - Liu, Jie; Chen, Hulin; Wu, Dewei; Wei, Ruiling; Lv, Chaolan; Dong, Juan; Wu, Dandan; Yu, Yue
Abstract : Background . Stimulant laxatives are still considered the most common treatment for functional outlet obstruction constipation (FOOC). However, the effectiveness of laxatives is unsatisfactory, and the long-term use of laxatives may cause certain adverse events. With this in mind, it is, however, paramount that novel complementary treatment(s) and/or other forms of alternative medicine are adequately investigated. Aims . The study aims to explore the effects and potential mechanism(s) of transcutaneous electrical acustimulation (TEA) combined with adaptive biofeedback training (ABT) on FOOC. Methods . A total of forty-five patients with FOOC were recruited and were randomly assigned to receive either Macrogol 4000 Powder (MAC, 10 g bid) (group A, n = 15) only, ABT + MAC + Sham-TEA (group B, n = 15), or TEA + ABT + MAC (group C, n = 15) in a six-week study. Individual patients' constipation-symptoms (PAC-SYM) and constipation-quality of life (PAC-QOL) were both assessed and scored. Serum acetylcholine (Ach) and nitric oxide (NO) were measured from drawn blood samples while individual patients' heart rate variability (HRV) was calculated at baseline and after each corresponding therapy. Anorectal manometry and balloon expulsion test were both performed before and after treatment. Results . Firstly, participants in group C had significantly lower scores of PAC-SYM, PAC-QOL, and a decreased anal defecating pressure (ADP) as compared to participants in group B (all p < 0.050 ). These results, however, suggest the TEAs effect. Secondly, the low-frequency band (LF)/(LF + HF) ratio in groups B and C were decreased as compared to group A (p = 0.037, p = 0.010, respectively) regarding HRV. On the other hand, the high-frequency band (HF)/(LF + HF) ratio in groups B and C showed an opposite outcome. Finally, the serum Ach in groups B and C was significantly higher as compared to group A (p = 0.023, p = 0.012, respectively). Of significant importance, the serum NO in groups B and C were notably low as compared to group A (p = 0.001, p < 0.001, respectively). Conclusions . TEA, combined with ABT, effectively improves constipation symptoms as well as QOL in FOOC patients. It is, however, achieved by decreasing ADP, which mechanisms are mediated via the autonomic and enteric mechanisms.